2003
DOI: 10.1002/pi.1138
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antitumour activity of medium molecular weight phthalimide polymers of camptothecin

Abstract: Attachment of anticancer agents to polymers has been demonstrated to improve their therapeutic profiles. A new monomer containing camptothecin, 5-norbonene-endo-2,3-dicarboxylimidoundecanoyl-camptothecin (NDUCPT) and its homopolymer and copolymer with acrylic acid (AA) were synthesized and spectroscopically characterized. The NDUCPT content in poly(NDUCPT-co-AA) obtained by elemental analysis was 51%. The average molecular weights of the polymers determined by gel permeation chromatography were as follows: M n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Theodorakis and co-workers developed phthalimide-co-acrylic acid polymers synthesized through photopolymerization to afford a 25.5 kDa (Figure 7) construct with 21 wt % CPT in one derivative 275 or a 15.4 kDa construct with 26 wt % CPT in another. 276 In ViVo studies with the high molecular weight polymer architectures showed an increase in activity compared to free CPT. Doses of 10 mg/kg of CPT, 21 mg/kg CPT equivalents in the polymer or 2.1 mg/kg CPT equivalents in the polymer afforded ∼90 day survival time.…”
Section: Sn-38 Liposomes (Le-sn-38) Animal Modelsmentioning
confidence: 96%
See 1 more Smart Citation
“…Theodorakis and co-workers developed phthalimide-co-acrylic acid polymers synthesized through photopolymerization to afford a 25.5 kDa (Figure 7) construct with 21 wt % CPT in one derivative 275 or a 15.4 kDa construct with 26 wt % CPT in another. 276 In ViVo studies with the high molecular weight polymer architectures showed an increase in activity compared to free CPT. Doses of 10 mg/kg of CPT, 21 mg/kg CPT equivalents in the polymer or 2.1 mg/kg CPT equivalents in the polymer afforded ∼90 day survival time.…”
Section: Sn-38 Liposomes (Le-sn-38) Animal Modelsmentioning
confidence: 96%
“…276 In vivo studies with the high molecular weight polymer architectures showed an increase in activity compared to free CPT. Doses of 10 mg/kg of CPT, 21 mg/kg CPT equivalents in the polymer or 2.1 mg/kg CPT equivalents in the polymer afforded ~90 day survival time.…”
Section: Macromolecular Architectures For Passive Drug Deliverymentioning
confidence: 98%
“…If a drug molecule contains hydroxyl or amino groups, a polymeric drug is best prepared through the reaction of the drug with a presynthesized polymer with functional side groups able to react selectively with the aforementioned groups and produce ester or amido bonds 1, 3. Several activated esters and amides of acrylic acid, methacrylic acid, and their polymers have been described 4–9. In our previous work, we described the synthesis, polymerization, copolymerization, and exchange reactions of acrylic and methacrylic esters 10–16.…”
Section: Introductionmentioning
confidence: 99%
“…One promising approach for targetable drug delivery is the use of polymers. Recently, several activated polymers containing phthalimido moiety have been used as macromolecular drugs (Orzeszko et al , 2000; Lee et al , 2002, 2003; Lee and Theodorakis, 2003). One of the more interesting topics in the field of pharmacologically active polymers is the preparation of polymeric drugs in which drugs are attached to the polymeric backbone via covalent bonds with limited stability to biological environments (Ferruti and Vaccaroni, 2003; Ferruti et al , 1978).…”
Section: Introductionmentioning
confidence: 99%